Leafhopper subfamily Hylicinae (Hemiptera: Auchenorrhyncha: Cicadellidae) in the Indian subcontinent with description of new species - Viraktamath, C. A.; Yeshwanth, H.m. (Zootaxa, 2023)
The genera and species of Hylicinae reported from the Indian subcontinent are reviewed. Hatigoria zhangi sp. nov. (India: Arunachal Pradesh), Hemisudra indica sp. nov. (India: Manipur), Kalasha confusa sp. nov. (India: Meghalaya), Kalasha manikya sp. nov. (India: Manipur) and Sudra manipurensis sp. nov. (India: Manipur) are described. Genera Hemisudra Schmidt, Hatigoria Distant and Sudra Stål are new records for India. All the taxa dealt with are illustrated and diagnosed, new taxa are described and illustrated. A revised diagnosis of the subfamily Hylicinae is provided. A revised key to Hylicinae genera of the Indian subcontinent and a checklist are also provided.